Induced polygenic variability in sesame by combining hybridization and recurrent mutagenesis in F3M3 generation (Bangladesh Journal of Botany, 2020)
The investigation was made to estimate the combined effects of hybridization and ethyl methane sulphonate (EMS) induced mutagenesis on the variability of seed yield and its attributes in F3M3 generation. A total of 15 populations were grown in randomized block design (RBD) with three replications. F3M3 results indicated an increase in variability for plant height, number of capsules per plant and seed yield per plant, whereas non significant variability was observed for number of primary branches per plant in mutant populations than respective controls. Increased mean value and increase in variability in the present investigation denoted the occurrence of more favorable mutations and breaking up of undesirable linkages with enhancing recombination. Correlation study in F3M3 generation indicated remarkable changes among seed yield per plant and its component traits and these changes might have come through independent polygenic mutations and enhanced recombination of polygenes affecting different traits. The outcome of this study will facilitate in understanding the effectiveness of combined effects of hybridization and EMS induced mutagenesis for sesame improvement.